MANAJEMEN PENGELOLAAN BARANG MILIK DAERAH MENUJU OPINI WAJAR TANPA PENGECUALIAN (WTP)(Studi Kasus pada Pemerintahan di Kabupaten Provinsi Kalimantan Barat) - Nina Febriana Dosinta, Reiza Apriadinihari, Haryono, (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2020)
This study aims to understand the process of managing Regional Property (BMD) in district governments that have not yet obtained an Unqualified Opinion in audits conducted by the Supreme Audit Board (BPK) and to analyze the causes of regional property management problems. This research is a qualitative case study research with data collection techniques through observation, interviews, and documentation studies. The results showed that in the management of the regional property, the local government had carried out in accordance with statutory provisions, namely the Regulation of the Minister of Home Affairs Number 19 of 2016 concerning Guidelines for the Management of Regional Property. From the research results also obtained the results of the analysis of the causes of regional property management problems in the district government, namely in human resources. In addition, the lack of coordination between related work units, the inadequate inventory process and inadequate documentation are also the problems found in this study.Keywords: Regional Property Management, Opinion of Supreme Audit Board of the Republic of Indonesia.